Recycling of Animal By-Products: Composition and Nutritional Value of Hydrothermally Hydrolyzed Bovine Hair - Mora-Maldonado, Luz Elena (2020)
[Introduction]: Bovine hair, a by-product of the hide transformation process, is rich in keratin protein. However, it is little used, and its final disposal is, generally, the sanitary landfill. [Objetive]: This work promotes its recycling, through its transformation into a food product for animals, applying a hydrothermal hydrolysis process. [Methodology]: For this, the hair was collected in a local tannery, washed, milled (<0.84 mm), and hydrolyzed (130 °C/2.0 atm/90 min). Later, it was characterized in its elemental analysis, thermogravimetric analysis, proximal analysis, and microbiological quality. The presence of heavy metals and minerals was determined by induction-coupled plasma atomic-emission spectrometry and, the amino acid profile, by high-performance liquid chromatography. [Results]: With the proposed process, hydrolyzed bovine hair was free of unpleasant odor, and with smooth and homogeneous texture. Its thermal stability was less than 170 °C. It presented an elemental content of nitrogen (13.80±0.61 %), carbon (46.23±1.18 %) and, sulfur (2.00±0.13 %). The proximal analysis revealed the following compositions (%): crude protein (85.2±2.5 %), digestible in pepsin (71.36±2.9); ash (2.20±0.1), ether extract (4.90±0.4), nitrogen-free extract (0.17±0.01) and, humidity (7.53±0.2). Some minerals were found (calcium, potassium, phosphorus). Heavy metals and Salmonella spp were not detected. Essential amino acids for animal nutrition (lysine, methionine, threonine, arginine and, valine) were obtained, with recoveries greater than 90 %. [Conclusions]: Based on this information, residual bovine hair can be recycled, for transformation to an alternative food product, which provides nutrients (protein/amino acids), for animal feed.